Programming of urban revitalization = Programowanie rewitalizacji obszarów miejskich - Biliński, Tadeusz (1932- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The planning stage of the investment?construction process is of a crucial importance. Its overall impact on the costs, construction time and the quality of design solutions is huge. However, in practice, little attention is given to this pre-design stage, except for public buildings or other buildings of particular importance.
Keywords: revitalization; importance; town renewal; rewitalizacja; programowanie; odnowa miast